2019
DOI: 10.1111/jfpp.14085
|View full text |Cite
|
Sign up to set email alerts
|

Microwave–vacuum drying of pomegranate arils ( Punica granatum L. cv. Hicaznar): Effect on quality and nutrient content

Abstract: In this study, microwave-vacuum drying of pomegranate arils (Punica granatum L. cv. Hicaznar) was investigated and the effect of microwave power and vacuum level on some quality and nutritional characteristics was determined by the response surface methodology. The drying experiments were conducted at three levels of microwave power (50, 100, and 150 W) and three levels of vacuum level (40, 75, and 110 mbar (abs)) employing a face-centered composite design. Dried arils were analyzed for some physical (hue angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Also, the microwave heating causes the faster heating rates due to the volumetric heat generation in which the microwave energy absorbed from the food material is converted into heat (Gowen, Abu-Ghannam, Frias, & Oliveira, 2006). Previously, the microwave-assisted hot air convective drying (Staniszewska et al, 2020), the combined microwave-vacuum drying (Süfer & Palazo glu, 2019) and microwave-assisted spouted bed drying (Serowik et al, 2018) have been applied to reduce the length of drying time and energy consumption.…”
mentioning
confidence: 99%
“…Also, the microwave heating causes the faster heating rates due to the volumetric heat generation in which the microwave energy absorbed from the food material is converted into heat (Gowen, Abu-Ghannam, Frias, & Oliveira, 2006). Previously, the microwave-assisted hot air convective drying (Staniszewska et al, 2020), the combined microwave-vacuum drying (Süfer & Palazo glu, 2019) and microwave-assisted spouted bed drying (Serowik et al, 2018) have been applied to reduce the length of drying time and energy consumption.…”
mentioning
confidence: 99%
“…As the samples dried by HTAD at 70 °C obtained the lowest ∆E * ab value, their color values were close to fresh fruit. Tere is a strong correlation between the perception of the color by consumers and the hue angle value, which is consequently regarded as a qualitative characteristic of color [76]. Te orange color of orange fruits (both peel and fesh) essentially comes from carotenoids and is characterized by a higher hue angle.…”
Section: Color Propertiesmentioning
confidence: 99%
“…Sablani et al [60] reported that blanching treatment before air-drying increased the retention of phenolic and total anthocyanin content in dried berries which is in agreement with the findings from our study. Furthermore, lower TAC observed for unblanched arils could be attributed to greater destruction of phenolic compounds which could change their chemical structure due to the thermal process [61,62].…”
Section: Total Phenolic Content (Tpc) and Total Anthocyanin Content (mentioning
confidence: 99%